Induction Chemotherapy and Ablative Stereotactic Magnetic Resonance Image-Guided Adaptive Radiation Therapy for Inoperable Pancreas Cancer - Chuong, Michael D.; Herrera, Roberto; Kaiser, Adeel; Rubens, Muni; Romaguera, Tino; Alvarez, Diane; Kotecha, Rupesh; Hall, Matthew D.; McCulloch, James; Ucar, Antonio; DeZarraga, Fernando; Aparo, Santiago; et al. (Frontiers in Oncology, 2022)
Background: Radiation therapy (RT) dose for inoperable pancreatic ductal adenocarcinoma (PDAC) has historically been non-ablative to avoid injuring gastrointestinal (GI) organs at risk (OARs). Accruing data suggest that dose escalation in select patients may significantly improve clinical outcomes. Early results of ablative stereotactic magnetic resonance image-guided adaptive radiation therapy (A-SMART) have been encouraging although long-term outcomes are not well understood. Methods: A single institution retrospective analysis was performed of inoperable non-metastatic PDAC patients who received induction chemotherapy then 5-fraction A-SMART on a 0.35T-MR Linac from 2018-2021. Results: 62 patients were evaluated with median age 66 years (range 35-91) and nearly all ECOG performance status 0-1 (96.8%). Locally advanced disease was common (72.6%), otherwise borderline resectable (22.6%) or medically inoperable (4.8%). All received induction chemotherapy for a median 4.2 months (range, 0.2-13.3) mostly commonly FOLFIRINOX (69.4%). Median prescribed dose was 50 Gy (range 40-50); median biologically effective dose (BED10) was 100 Gy10. Median and 2-year local control (LC) from diagnosis were not reached and 68.8%, respectively. Median and 2-year progression-free survival (PFS) from diagnosis were 20 months and 40.0%, respectively. Median and 2-year overall survival (OS) from diagnosis were 23 months and 45.5%, respectively. Acute and late grade 3+ toxicity rates were 4.8% and 4.8%, respectively. Conclusions: To our knowledge, this is the largest series of induction chemotherapy followed by ablative 5-fraction SMART delivered on an MR Linac for inoperable PDAC. The potential for this novel treatment strategy to achieve long-term LC and OS compared to chemotherapy alone warrants prospective evaluation.